Influence of anodizing variables on Cr (VI) photocatalytic reduction using TiO2 nanotubes obtained by anodic oxidation - Dwojak, Anabela Natalia (2017)
Fil: Dwojak, Anabela Natalia. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Materiales de Misiones; Argentina.